Eficiência de fertilizantes organominerais no desenvolvimento inicial de milho e feijão - Maranho, Jussiguelli Marcondes (2019)
Bean plant is one of the main crops of economic importance in Brazil, being a plant considered demanding in fertility and soil quality, due to the short cycle and the superficial root system and little developed. Therefore, it is important that the nutrients are readily available to plants, according to demand during the cycle. Organomineral fertilizers are sustainable sources of plant nutrients, as they are needed, reducing environmental impact and being a viable alternative for producers. The objective of this work was to evaluate the agronomic efficiency of organomineral fertilizers in the sowing of common bean cv. Carioca, in the V4 / R5 stages. The experiment was carried out in the area of the University Center of Triângulo-UNITRI, located in the city of Uberlândia-MG. The variety chosen was the Carioca bean, indeterminate type, with a cycle of 90 days. The experimental design was DBC in 4 replications. The plots consisted of 6 lines of 3 meters spaced by 0.5 meters and 5 meters plot width, with a total plot of 15 m2 and a useful plot of 2 central lines. The treatments were: T1 - control (without fertilization); T2 - FM 90 kg ha-1 of P2O5; T3 - FOM 150 kg ha-1 of P2O5; T4 - FOM 180 kg ha-1 of P2O5; T5 - FOM 360 kg ha-1 of P2O5; T6 - FM 180 kg ha-1 of P2O5. At 15 DAS the seedling emergence evaluation was carried out; and at 30 DAS were measured the variables diameter, height, fresh mass and dry mass of 10 plants of the useful plot. The results were submitted to analysis of variance and regression for the doses of organomineral, and Dunnet to compare the mineral and organomineral sources. The fertilization with organomineral fertilizer applied at sowing increased the initial growth of the bean, for variables diameter, height, fresh and dry mass. It was concluded that the fertilization with organomineral fertilizer based on filter cake has superior efficiency to the mineral fertilization as source of phosphorus. The dose of organomineral fertilizer that resulted in the highest initial growth of bean was 360 kg ha-1 of P2O5.